2017: роман / Ольга Славникова - Славникова Ольга Александровна (Вагриус, 2008)
Экземпляры: ф.4 (2009) / Инвентарный номер: 52892 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: С 47 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44